Diagnosis, pharmacotherapy and cognitive behavioral therapy of trichotillomania - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2011)
Diagnosis, pharmacotherapy and cognitive behavioral therapy of trichotillomania Trichotillomania is defined as significant hair loss due to individuals' repetitive self-pulling of hair. It is a chronic disorder that leads to significant distress and functional impairment and is often difficult to treat. Although it has been recognized for a long time, it has attracted less attention from scholars compared to other psychiatric disorders. Despite the fact that it is classified as an impulse control disorder, there is still a debate on how it should be classified. Research regarding etiology and treatment of trichotillomania has increased over last twenty years. It has been mentioned that its etiology is based on evolutional, genetic, neurophysiological and neurocognitive factors. Although robust evidence is not available, drugs such as clomipramine and selective serotonin reuptake inhibitors (SSRIs) or cognitive behavioral therapy are promising treatments. Habit Reversal Training (HRT), as a cognitive behavioural technique, has the highest rate of success in treating trichotillomania. However, not revealing the the habit of pulling hair or not coming forward to seek help due to embarrassment is an obstacle to running large scale controlled experiments. A series of multi-centered, coordinated large scale studies are needed to explore the etiology of the disorder, reach an agreement on its classification and defining the best approach and algorithms for the treatment. In this review it is aimed to summarise the latest research and progress in etiology classification and treatment of trichotillomania.
Keywords: Trichotillomania; Habit Reversal Training (HRT); cognitive behavioral therapies; pharmacotherapy; OBSESSIVE-COMPULSIVE DISORDER; HABIT REVERSAL; DOUBLE-BLIND; DESCRIPTIVE PSYCHOPATHOLOGY; BASAL GANGLIA; HAIR; COMORBIDITY; FLUOXETINE; CHILDREN; SCALE